Simulation of the time-dependent dynamical diffraction of FEL X-ray pulses - Sheppard, J; Lee, R; Wark, J (2001)
The temporal coherence properties of the X-ray pulse from a Free Electron Laser (FEL) will be altered during the process of dynamical diffraction from a perfect crystal. We present simulations of this process based on time-dependent dynamical diffraction theory. In addition, we present simulations of the diffraction of chirped X-ray pulses, demonstrating methods of pulse recompression by use of strained crystals.